The Challenges of Globalization to Linguistic Pan-Africanism and African Development - Ajayi, Samson Abiola (NIU Journal of Social Sciences; Vol 5 No 3 (2019): KIU Journal of Social Sciences, Vol. 5 No. 3, September 2019, 2019)
The latest but not the least of the challenges that confront efforts in linguistic pan-Africanism is that of globalization. This study underlines the importance of language in development and highlights efforts being made at different levels towards achieving linguistic pan-Africanism.  While being conscious of the dangers of narrow nationalism, the study recognizes a much more damaging danger in the imperialistic and neo-colonial phenomenon called globalization. Working in concert with multinational and world organizations such as World Bank, International Monitory Fund (IMF), World Trade Organization (WTO), globalization seeks to build a world system in which languages of lesser economies and powers have no relevance. Africa would have to navigate through these realities as it seeks to arrive at pan-African language(s) that would be truly African and serve as springboard for its much needed development. Keywords : Language, pan-Africanism, Globalization, Development, Nationalism.